Iodine-catalyzed sulfuration of isoquinolin-1(2H)-ones applying ethyl sulfinates. (12th March 2021) - Mu, Yangxiu; Yang, Minghua; Li, Fengxia; Iqbal, Zafar; Jiang, Rui; Hou, Jing; Guo, Xin; Yang, Zhixiang; Tang, Dong
Abstract : Sulfuration of isoquinolin-1(2 H )-ones at the C-4 position by employing ethyl sulfonates. Abstract : An efficient sulfuration of isoquinolin-1(2 H )-ones at the C-4 position is reported by employing ethyl sulfinates, and the corresponding products are obtained in moderate to excellent yields in the presence of iodine. This synthetic strategy provides a range of thioether-isoquinolin-1(2 H )-ones while tolerating a number of functional groups on the isoquinoline nitrogen atom and benzene ring. In addition, pyridin-2(1 H )-one is also reacted smoothly and afforded the corresponding thioether product in moderate yield. A plausible mechanism is suggested based on the preliminary mechanistic studies.